Is the Occurrence or Reversal of Nonalcoholic Fatty Liver Disease Associated with Long-Term Helicobacter pylori Infection among Chinese Adults? A Cohort Study. (24th November 2021) - Zhao, Xia-Xia; Wang, Rui-Ling; Liu, Ming-Hao; Huang, Xiao-jun
Abstract : Background . Previous studies have suggested a link between Helicobacter pylori (H. pylori) infection and nonalcoholic fatty liver disease (NAFLD), yet long-term follow-up studies to elucidate this association are lacking. We aimed to identify the relationship between NAFLD and H. pylori in these people. Methods . A total of 2, 934 adults between June 2013 and October 2017 were collected; among them, 675 people met the requirements. People were assessed for H. pylori infection diagnosis as detected by the carbon-13 urea breath test; they were also assessed for NAFLD diagnosis by ultrasound. Results . H. pylori infection was present in 206 patients (30.5%), and 469 (69.5%) participants were classified as controls. Participants with H. pylori infection had a higher rate of incident NAFLD than those who were uninfected (37/206; 18% versus 73/469; 15.6%) (p < 0.001 ). Compared with the control group, the recovery rate of NAFLD in the H. pylori+ve group was low (6/206, 2.9% versus 33/469, 7.0%) (p < 0.001 ). Besides, the incidence of uric acid, postprandial blood glucose, TG, LDL-C, HDL-C, and fasting plasma glucose was significantly different between the two groups (p < 0.001 ), but no difference was found in alanine aminotransferase (ALT), liver-total protein, urea nitrogen, and cholesterol (p > 0.05 ). Conclusion . H. pylori infection was a risk factor for NAFLD and affected the occurrence or reversal of NAFLD, indicating that H. pylori infection eradication might play a role in reducing the risk of NAFLD.